A semi-analytical method for determining the optimal stripper pressure in CO2 capture and liquefaction using monoethanolamine (MEA). (March 2016) - Park, Taekyoon; Lee, Seok Goo; Kim, Sung Ho; Lee, Ung; Han, Chonghun; Lee, Jong Min
Abstract : Graphical abstract: Abstract : Highlights: Design an integrated CCS simulation model from power plant to storage. Develop a new algorithm for determining the optimal stripper pressure. Solve an optimization problem without a repetitive simulation. Consider energy efficiency and savings to suggest optimal pressure values. Abstract: The operation pressure of a distillation column is one of the key variables in optimizing the required energy in a carbon capture and storage (CCS) chain. It affects the steam drag point in power plants, the regeneration energy in capture process and the compression energy in the liquefaction process. A new semi-analytical method for determining optimal stripper pressure for the CCS process using MEA as an absorbent is proposed based on the integrated simulation model. Total required energy is represented as a function of the pressure based on the equivalent work. Two different method – simultaneous and sequential – are applied to solve the optimization problem. The results show that the total energy has a monotonous decreasing function with respect to the stripper pressure and the higher stripper pressure is favorable when a terminal pressure is above 10 bar. When the terminal pressure has a small value near 5 bar, the total energy shows a convex form and the optimal stripper pressure is located between 1 and 2.2 bar.